Fastering Humanistic Language Teaching - Jumadi (Indonesian Journal of Education Methods Development, 2019)
Language teaching systems (especially in Indonesia) are generally still dominative. Teachers still dominate teaching process, both regarding the communication pattern, material presentation, and evaluation system used. In fact, education experts, such as John Dewey and Paulo Freire, emphasize the importance of developing a humanistic teaching climate. In this teaching climate, teachers place students as human beings who prepare their future critically and creatively. Teachers’ domination means killing students' criticality and creativity. Humanization of language teaching can be represented in various aspects of teaching, including in the process of preparing teaching materials, processes, and evaluation.